A model for the rubber-llke behaviour in CU-Zn-Al martensitea. - Ahlers, Manfred Hermann; Barceló, G. N.; Rapacioli, R. (Pergamos Press, 1978)
Fil: Ahlers, M. Comisión Nacional de Energía Atómica; Argentina